Human values and education - Ruhela, satya Pal. (New Delhi : Sterling publishers, 1990)
1. Concept Of Value 2 Axiology And Education 3. Idealism Naturalism And Values 4. Realism Pragmatism And Values 5. Bhartiya Dharma And Education 6 Comparison Dharma And Religion 7. Bhartiya Cuture 8 Hierarchy Of Social Values 9 Ecological Values 10. Universal Values 11. Human Values And Education 12.Value Oriented Education 13. Values And Educational Aims 14. Pedagogics Of Value Education 15.School System For Value Education 16 Qualities Of Teacher For Value Education 17.Measurement And Evaluation Of Values 18 Research Studies In Value: Education
Includes bibliography.
Keywords: Moral education -- India